In the World of Vlad The Lives and Times of a Warlord. - Simon, Alexandru (Berlin : Frank & Timme, 2021)
Long description: The life (in fact the lives) of Vlad III "the Impaller" or "Dracula" is a Rorschach test. Everybody sees what they want to see in the "documentary stains". And these "stains" are expanding. Based on research in the archives and libraries of Budapest, Dubrovnik, Genoa, Mantua, Milan, Modena, Munich, Rome, Venice and Vienna, the book focuses on the conflictive medieval, and modern images created by the clash between the classical pictures of Vlad and the still preserved coeval sources.
Biographical note: Alexandru Simon is Research Professor at the Centre for Transylvanian Studies of the Romanian Academy in Cluj-Napoca. His recent publications include: "Valachorum regulus" (2017), "Re de Dacia" (2018, with Ioan-Aurel Pop), and as co-editor "Reform and Renewal in Medieval East and Central Europe (2019, with Suzana Miljan and Éva B. Halász).
The "Pawns" and "Pillars" of Crusading -- Mehmed II's Return to Moldovia in 1476 and the Death of the King of Dacia -- An Imperial Order issued in the Land of the Wallachians -- The Un-credited Victory over the Sultan -- A King dies -- Voivode Dracula between Matthias Corvinus' Dacia and Nicholas of Modruš' Gothia -- The Infamous Wallachian Instrument of the Low-born Hunyadi Monarch -- Vlad III and Matthias Corvinus' Kingdom of Dacia -- The Roman Arrogance of the Primitive Wallachians -- Exercito di Bayseto in Valachia, roto da Uracula Wayvoda
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Vlad -- III, -- Prince of Wallachia, -- 1430 or 1431-1476 or 1477.; Wallachia -- Kings and rulers -- Biography; Kings and rulers; Rois et souverains